Analysis of Elementary School Teacher Education Students' Errors in Solving Mathematical Problems Based on Newman's Theory - Muhassanah, Nur'aini; Nurcahyono, Novi Andri (RANGE: Jurnal Pendidikan Matematika, 2025)
This study aims to describe students' errors in solving math problem solving based on Newman's theory. This research method is qualitative with a case study approach. The subjects of this study were 18 students of the Elementary School Teacher Education Study Program in the odd semester of the 2023/2024 academic year who took Mathematics courses. Data related to student errors according to Newman's theory were obtained from tests and interviews to identify the types of errors made by students, which included errors in reading, understanding, transformation, process skills, and writing the final answer. Subjects were taken using purposive sampling technique and data validation using method triangulation. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The results of this study showed that the most student errors made were process errors as much as 32.97% with fairly high criteria followed by errors in writing the final answer as much as 29.67%, transformation errors as much as 27.47% which were included in the criteria quite high and the last error understanding the problem as much as 9.89% with very low criteria. Based on the results of the study, it is suggested that students should practice more independently working on problems, especially story problems. In addition, before working on the problem, students should first write down the complete information in the problem.